Problematika Kemampuan Membaca Al-Qur’an Siswa dalam Aspek Tajwid serta Dampaknya terhadap Kepercayaan diri Siswa di MTS Negeri 2 Pekalongan - Irsilawati Dewi; Nadiatus Sarifah; Salwaa Durrotun Nashah; Fina Khilyatu Zahwa; Azzakiya Aufa Shalina; M. Fahmy Fredyansyah Maulana; Muhammad Muhaimin Muhammad Muhaimin; Syahrul Ardiansyah; Rofiqotul Aini (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study aims to analyze the problems of students’ ability in reading the Qur’an, particularly in the aspect of tajwid, and its impact on students’ self-confidence at MTs Negeri 2 Pekalongan. This research employed a qualitative descriptive approach. The data were collected through observation, interviews, and documentation involving Qur’an Hadith teachers, BTQ and Tahfidz teachers, and seventh-grade students. The findings revealed that most students were able to read the Qur’an fluently; however, several students still experienced difficulties in applying tajwid rules, makharijul huruf, and distinguishing long and short pronunciations. These difficulties were influenced by students’ learning environment, Qur’anic learning habits, participation in TPQ or Islamic boarding schools, and family support. The study also found that students with good Qur’an reading skills tended to have higher self-confidence, were more active, and were more willing to perform in front of the class. In contrast, students with lower reading abilities often felt shy, nervous, and lacked confidence. To overcome these problems, teachers implemented several strategies such as gradual tahsin learning, memorization submission, peer tutoring, hijaiyah educational games, and continuous motivation. These strategies were considered effective in improving both Qur’an reading skills and students’ self-confidence.